2007
DOI: 10.1073/pnas.0707351104
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-suppressive miR-34a induces senescence-like growth arrest through modulation of the E2F pathway in human colon cancer cells

Abstract: Accumulating evidence suggests a role for microRNAs in human carcinogenesis as novel types of tumor suppressors or oncogenes. However, their precise biological role remains largely elusive. In the present study, we aimed to identify microRNA species involved in the regulation of cell proliferation. Using quantitative RT-PCR analysis, we demonstrated that miR-34a was highly up-regulated in a human colon cancer cell line, HCT 116, treated with a DNAdamaging agent, adriamycin. Transient introduction of miR-34a in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

37
717
3
6

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 879 publications
(763 citation statements)
references
References 39 publications
37
717
3
6
Order By: Relevance
“…Activation of miR-34a by p53 normally promotes cell-cycle arrest through the modulation of E2F protein expression (He et al, 2007;Raver-Shapira et al, 2007;Tarasov et al, 2007). Further, it was shown that introduction of miR-34a into cancer cells suppressed their growth in vivo, thereby demonstrating the potency of this tumor-suppressive miRNA (Tazawa et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of miR-34a by p53 normally promotes cell-cycle arrest through the modulation of E2F protein expression (He et al, 2007;Raver-Shapira et al, 2007;Tarasov et al, 2007). Further, it was shown that introduction of miR-34a into cancer cells suppressed their growth in vivo, thereby demonstrating the potency of this tumor-suppressive miRNA (Tazawa et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…3) and reduced levels of the tumor-suppressor miRNA have been observed in a variety of cancer types, including liver cancer (4,5). When introduced into cancer cells, miR34a induces cell-cycle arrest (6), senescence (7), and apoptosis (7). The miRNA also inhibits cancer stem cell development (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous studies have demonstrated that a number of miRNAs are also involved in tumor pathogenesis and the development of different types of human cancers, including cervical (17), ovarian (8,18), lung (19), breast (9), colon (10), and prostate cancers (12).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that miRNAs are aberrantly expressed in different cell types and at different developmental stages, suggesting that miRNAs play important roles in cell growth (8)(9)(10)(11)(12), differentiation (13,14), metabolism (15), and programmed cell death (16). Moreover, previous studies have demonstrated that a number of miRNAs are also involved in tumor pathogenesis and the development of different types of human cancers, including cervical (17), ovarian (8,18), lung (19), breast (9), colon (10), and prostate cancers (12).…”
Section: Introductionmentioning
confidence: 99%